Biological synthesis of 2, 5-bis(hydroxymethyl)furan from biomass-derived 5-hydroxymethylfurfural by E. coli CCZU-K14 whole cells. (January 2018) - He, Yu-Cai; Jiang, Chun-Xia; Chong, Gang-Gang; Di, Jun-Hua; Ma, Cui-Luan
Graphical abstract: Highlights: Highly 5-HMF-tolerant recombinant strain E. coli CCZU-K14 was used for bioreduction. BHMF was biologically synthesized from 5-HMF with E. coli CCZU-K14 cells. CTAB facilitated the dispersal of substrate and increased the biocatalytic activity. β-Cyclodextrin enhanced the synthesis of BHMF and decreased the inhibition of 5-HMF. Biosynthesis of BHMF from 100 mM 5-HMF was obtained at 100% yield. Abstract: Biocatalytic upgrading of bio-based platform chemical 5-hydroxymethylfurfural (5-HMF) to 2, 5-bis(hydroxymethyl)furan (BHMF) is currently of great interest due to the product specificity, mild reaction and high efficiency. In this work, 200 mM 5-HMF could be effectively biotransformed to BHMF at 90.6% with highly 5-HMF-tolerant recombinant E. coli CCZU-K14 whole cells at pH 6.5 and 30 °C under the optimum reaction conditions (cosubstrate glucose 1.0 mol glucose/(mol 5-HMF), D -xylose 400 mM, l -glutamic acid 250 mM, Mg 2+ 1.5 mM, 0.2 mol β-cyclodextrin/(mol 5-HMF), CTAB (cetyltrimethyl ammonium bromide) 12.5 mM, and 0.1 g wet cells/mL). It was found that E. coli CCZU-K14 was highly tolerant to 5-HMF (up to 400 mM). Effective bioreduction of biomass-derived 5-HMF (≤200) to BHMF was successfully demonstrated in this study. In conclusion, this strategy showed high potential application for the synthesis of BHMF.